To issue of ecological safety quantitative evaluation at EIA - Статюха, Геннадій Олексійович; Соколов, Віталій Артемович; Абрамов, Ігор Борисович; Бойко, Тетяна Владиславівна; Абрамова, Алла Александровна (Eastern-European Journal of Enterprise Technologies, 2010)
The current state of ecological safety evaluation problem in design stage is analysed. Procedure of ecological safety estimation on the basis of index of objects danger and ecological risk is offered.